The franchise decision and financial performance: an examination of restaurant firms - Hsu, Li-Tzang (Jane) (Kansas State University, 2007)
In the last few decades, franchising has become a part of everyday life in the United States. Many firms in a variety of industries have adopted franchising as a method of doing business. Despite the importance of franchising, the literature on why firms initially choose to franchise and how franchising affects financial performance has been scant (Combs et al., 2004; Watson et al., 2005). The purposes of this study were 1) to examine how well agency theory, resource scarcity theory, risk-sharing theory, and specific knowledge theory justify the franchising decision, 2) to investigate whether franchising affects restaurant firms' market value and profitability, and 3) to investigate the relationship between the ownership mix, combination of franchised and company-owned outlets, and financial performance. For the statistical analysis, the data were collected from the Standard and Poor's COMPUSTAT database, Bond's Franchise Guide and 10 K reports. A logistic regression model was developed to identify a set of variables that best differentiated firms engaged in franchise contracts from those that were not. The statistical results indicated that: 1) Young and growing firms used franchise more to increase the flow of resources. This result supported resource scarcity theory. 2) The degree of geographic dispersion and involvement in foreign countries increased the probability of a firm's decision to franchise. These results supported agency theory. 3) The decrease of specific knowledge requirements increased the franchising probability. This result supported specific knowledge theory. T-tests and multivariate regression models were used to test how franchising affects firms' financial performance. The findings indicated that 1) franchised firms had better financial performance than non-franchised firms, 2) the relationship between ownership mix and financial performance was curvilinear and the inverted U-shaped relationship suggested the existence of optimal ownership mix that can maximize a firm's financial performance, and 3) ownership mix not only directly affected a firm's intangible assets, but also indirectly affected a firm's intangible assets through advertising. This study found that a purely company owned or a purely franchised chain did not produce the best financial performance. Restaurant companies could use both company-owned and franchised units to leverage the strengths of one another, which will yield a better overall financial performance than if either structure was to operate alone.
Keywords: Franchising; Restaurant; financial performance; Agency theory; Resource scarcity; Business Administration, Accounting (0272); Business Administration, Management (0454)